Myodes glareolus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
49. Bank Vole Mpyodes glareolus French: Campagnol rousséatre / German: Rotelmaus / Spanish: Topillo rojo Taxonomy. Mus glareolus Schreber, 1780, Island of Lolland, Denmark. Throughout the 20" century, glareolus was included in FEvotomys or Clethrionomys; both generic names are junior synonyms of Myodes. Myodes glareolus is more closely related to M. centralis and M. macrotis than to M. rutilus. Past and present hybridization with M. rutilus was documented in the zone of sympatry, and all individuals with alien mitochondrial genome are M. glareolus. Large number of subspecific names was proposed for M. glareolus, but they were never revised. Some sources list 26 subspecies in western Europe alone, while others recognized 10-13 subspecies from the entire distribution. Phylogeographic studies using molecular markers retrieved complex evolutionary history and survival in multiple glacial refugia. Monotypic. Distribution. W Europe from Atlantic coast E to Yenisei River, N border set by Arctic tundra and S border ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 302-303, DOI: 10.5281/zenodo.6707142 ...